2015
DOI: 10.1109/tvcg.2014.2371858
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Color and Leader Line Highlighting Strategies in Coordinated View Geovisualizations

Abstract: In most coordinated view geovisualization tools, a transient visual effect is used to highlight observations across views when brushed with a mouse or other input device. Most current geovisualization and information visualization systems use colored outlines or fills to highlight observations, but there remain a wide range of alternative visual strategies that can also be implemented and compared to color highlighting to evaluate user performance. This paper describes the results of an experiment designed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…Most of the market-available mobile devices rely on touch functionality, and increasingly include support for voice and gesture input (Muehlenhaus, 2013). However, restriction to multimodal and touch input is a challenge in the context of exploratory visualization, where highlighting and coordinating using brushing is fundamental to successful interaction (Griffin & Robinson, 2015;Robinson, 2011). Furthermore, we need to consider how our interactive map and visualization designs should respond across mobile and non-mobile devices (Marcotte, 2010;Roth, 2015), requiring us to seamlessly design for every possible technology much like multiresolution databases and multiscale mapping now allow us to seamlessly design for every possible place and scale (Brewer & Buttenfield, 2007;Robertson, Ebert, Eick, Keim, & Joy, 2009).…”
Section: Looking Forward To Key Needs In Interactive Cartography and mentioning
confidence: 99%
“…Most of the market-available mobile devices rely on touch functionality, and increasingly include support for voice and gesture input (Muehlenhaus, 2013). However, restriction to multimodal and touch input is a challenge in the context of exploratory visualization, where highlighting and coordinating using brushing is fundamental to successful interaction (Griffin & Robinson, 2015;Robinson, 2011). Furthermore, we need to consider how our interactive map and visualization designs should respond across mobile and non-mobile devices (Marcotte, 2010;Roth, 2015), requiring us to seamlessly design for every possible technology much like multiresolution databases and multiscale mapping now allow us to seamlessly design for every possible place and scale (Brewer & Buttenfield, 2007;Robertson, Ebert, Eick, Keim, & Joy, 2009).…”
Section: Looking Forward To Key Needs In Interactive Cartography and mentioning
confidence: 99%
“…There is a wide range of available solutions that can be applied into the layout, highlighting being just one example (Robinson, 2011). Nevertheless, not all solutions are similarly effective and not all have been sufficiently exploited (Griffin and Robinson, 2015). It is therefore important to understand which features of CMV tools attract the attention of individuals who are learning the tools on their own, and which features the individuals refer to when seeking to understand a CMV's complex layout (as targeted in RQ3).…”
Section: Related Workmentioning
confidence: 99%
“…In this section, we define visual cues and review prior work on visual cues from different domains spanning from education, to psychology, to narrative visualization. Prior work in this domain has investigated visual cues by forming taxonomies [dKTRP09, LH10] studying the effectiveness of a single cue [THM*08], or comparing the effects of multiple cue types [GR10]. The prevalence of the presentation of results in various settings (e.g., academic conferences and business meetings) led us to focus on visual cues for presentation.…”
Section: Related Workmentioning
confidence: 99%
“…However, Moreno's study found that “improper use of cueing might be ineffective and even increase cognitive load on the learner” [dKTRP09, Mor07]. Works in other fields compared multiple visual cues [CCH*14, GR10] or studied combinations of visual cues [PO13, WPM16]. Pyysalo and Oksanen studied the effectiveness of cue combinations by comparing three highlighting conditions: size, size and shape, and size and color [PO13].…”
Section: Related Workmentioning
confidence: 99%